Features of the neurotropic effects of partial components of the balneotherapeutic complex of SPA Truskavets' - Andriy I Popovych (Kazimierz Wielki University, 2019)
Background. In the previous article we outlined the results of comparative evaluation of immunotropic effects of partial components of the balneotherapeutic complex of spa Truskavets'. In the previous article we outlined the results of comparative evaluation of neurotropic effects of partial components of the complex. Material and methods. The object of observation were the same 41 men and 10 women aged 24-70 years old, who came to the spa Truskavets' for the treatment of chronic pyelonephritis combined with cholecystitis in remission. We recorded simultaneously parameters of HRV and EEG before and after course of balneotherapy. 23 patients drank bioactive water Naftussya (BAWN); 7 others volunteers drank Ozokerite extract; 8 patients in the third group received BAWN and baths with mineral water and for the other 13 patients in the balneotherapeutic complex included additionally application of Ozokerite on the lumbar region Results. It has been shown that the use of the water solution of Ozokerite dramatically increases the vagus tone and reduces the reciprocally the sympathetic tone, which is accompanied by an increase in the Amplitude of both β- and δ-rhythms as well as in the Frequency of the latter, on the one hand, and a decrease in the Index and the Deviation of θ-rhythm as well as the Amplitude of α-rhythm, on the other hand. At the same time, there is a left-sided shift in the Laterality of β- and α-rhythms. Instead, the Microbiota of Naftussya water, together with the transformed by microbes of organic substances that are related to Ozokerite, have the same pronounced but opposite effect on the listed parameters of HRV and EEG. As a result, BAWN, which contains both neurogenic antipodes in its composition, has a very moderate neurotropic effect on the listed parameters of HRV and EEG. Mineral baths activate other vagus tone markers and suppress the sympathetic marker, coupled with a decrease in the Entropy of HRV bands and β-rhythm Frequency, as well as a significant left-sided shift in Laterality both θ- and δ-hythms. The consistent use of BAWN somewhat weakens the listed effects of Baths due to the slight opposite effect of its organic substances, but not Microbes. Instead, the application of organic substances to the skin causes a much more pronounced opposing neurotropic action. Organic substances of Ozokerite, applied to the skin, causes a increase in Bayevskiy's ARS Index as well as vagal tone and a decline in Bayevskiy's Stress Index coupled with a decrease in Indexes both β- and α-rhythms. A similar, but much weaker effect makes contact with the skin of mineral water, while, as native and transformed by microbes organic matter on the side of the mucous of the digestive tract has the opposite effects on the listed parameters of HRV and EEG. Conclusion. The hypothesis that as native and transformed by microbes organic matter related to Ozokerite on the side of the gut activate chemoreceptors of vagus terminals and/or TL-Receptors of Macrophages of GALT. Activated Macrophages release cytokines, which too activate vagus afferents. When applying Ozokerite or taking Baths, organic substances and mineral salts activate the skin nerve terminals and/or TL-Receptors of Langerhans cells (as variety of Macrophages of SALT) which also release cytokines.